ANALISIS DAMPAK PEMILU TAHUN 2019 TERHADAP PASAR MODAL SYARIAH INDONESIA - Luthfi, Faishol; Ardelia, Aya Sofia; Mahmudi, Wildana Latif (Bangun Rekaprima, 2024)
Political events such as elections certainly have an impact on economic conditions, more specifically on the condition of the Indonesian sharia capital market. This research aims to analyze the impact of the election on the Indonesian sharia capital market in 2019. The quantitative approach used in this research includes the event study method and is followed by Wilcoxon test analysis. The data used in this research is JII share trading volume data from January to July 2019 on a daily basis as well as related research. JII share trading volume data will be observed and divided into: periods before observation, observation, and after observation. The research results show that there is a significant difference in the trading volume of JII shares between the periods before and after the observation, so it can be concluded that the election had an impact on the Indonesian sharia capital market. The recommendation for the government is to be able to create a safe and transparent election atmosphere considering that the implementation of the election will be the object of investor observation. Investor responses as a result of these observations will certainly influence macro economic conditions.